PERAN INDONESIA DALAM DIPLOMASI KEBUDAYAAN WISATA SELANCAR INTERNASIONAL OMBAK BONO RIAU TAHUN 2011-2014 - Ryan Zulmi; Saiman Pakpahan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research analyzes the role of Indonesia’s government, media and citizen oncultural diplomacy of Bono tidal bore, a newly developed international surfing tourism.Bono is located in Teluk Meranti village, Pelalawan regency, Riau province and offeringa special phenomenon that only available in four countries in the world. The promotionof Bono still fairly minimal since it just developed as a tourism region past few years.Like the other objects of cultural diplomacy such as Batik and Wayang, Bono tidal borewith all local tradition in the tourism region becomes new Indonesian cultural diplomacy.This case will be analyzed in state level of analysis within framework ofPerspective of Pluralist and Theory of Cultural Diplomacy. The theories explains thatnon-state actor have significant role in international politics including practice ofdiplomacy. Cultural diplomacy means all form of culture becomes instrument and alsoobject of diplomacy, mainly by state, as part of soft power and to gains the otheradvantageIndonesia rich of cultural products and needs cultural diplomacy to promote themto international society. The purpose can be international recognition and sertification,increasing tourist visits, and promotes the exellences of Indonesian. Through manyinternational forums, fairs, and electronic media, the government of Indonesia promotethe unique of Bono tidal bore to the world.Keywords: Bono tidal bore, Cultural Diplomacy, International Surfing Tourism.